Design Thinking Sebagai Metode Inovatif dalam Perancangan Aplikasi M-Physics - Nurussaniah, Nurussaniah; Batita, Maurish Sofie Rahmi; Ulfa, Saida; Praherdhiono, Henry; Sari, Ira Nofita (LP. Ma'arif Janggan Magetan, 2023)
In the ever-evolving digital era, learning applications have become indispensable tools in the educational process. This research delves into the utilization of Design Thinking as an innovative methodology for crafting M-Physics applications. The study delineates the steps involved in Design Thinking, which encompass empathy, definition, ideation, and prototyping. The findings demonstrate that Design Thinking aids researchers in gaining a deeper understanding of user needs, articulating problems more precisely, generating creative ideas, and ultimately, devising more innovative solutions. The foundation of the M-Physics prototype design lies in presenting material in a manner that is both succinct and detailed, aligning with the principles of generative learning. M-Physics aims to assist learners, particularly students, in comprehending physics material. Future research should endeavor to complete the Design Thinking process through to the testing stage, ensuring the production of a comprehensive product that truly meets user needs. The insights gleaned from this research are anticipated to be of value to other educational application developers seeking to incorporate a Design Thinking approach into their design processes.